Analisis Implementasi Kebijakan KPR BTN pada Perumahan Nugraha Asri di Kenagarian Tabek Panjang Kecamatan Baso Kabupaten Agam - Survio Dilla; Roni Ekha Putera (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study aims to determine and describe (1) analysis of the implementation of the BTN KPR Policy at Nugraha Asri Housing in Kenagarian Tabek Panjang, Baso District, Agam Regency. The results of the study show that (1) the PUPR has carried out its duties properly, based on the applicable terms and conditions, then provides recommendations for related parties in the acceptance or selection of subsidized housing, (2) KPR BTN, emphasizing on terms and conditions of borrowing and funding assistance, has emphasized to all consumers when entering into a contract, (3) PT. Mandevilla as the developer, played a major role in supporting the implementation of the subsidized housing target, so that in addition to prioritizing the sale of housing, it also provides convenience in management and also emphasizes the provisions of subsidized housing, (4) overall, consumers have entered the category the provisions of the people who are entitled to receive subsidized housing, it's just that there are various compelling circumstances for consumers, not being able to live in the housing that has been taken, ranging from family reasons, education, work and so on.